PENGARUH FINANCIAL TARGETS, INEFFECTIVE MONITORING, DAN RATIONALIZATION TERHADAP FRAUDULENT FINANCIAL REPORTING PADA SEKTOR KEUANGAN DI BEI TAHUN 2017—2019 - Vania Carolina Santoso Njotodiardjo (Ma Chung Press, 2021)
This study aims to determine the effect of financial targets, ineffective monitoring, and rationalization on the occurrence of fraud in financial reporting. The study was conducted on financial sector companies listed on the Indonesia Stock Exchange during 2017-2019. The number of companies that match the sample criteria in this study were 89 companies out of 105 companies in the financial sector. The analysis used is multiple linear regression analysis using SPSS. The results of the study indicate that the financial targets variable as proxied by ROA has a significant effect on fraudulent financial reporting, which indicates that the financial target variable is able to become a model to help detect fraud in financial reporting. Meanwhile, the ineffective monitoring variable which is proxied by the audit committee and the rationalization variable which is proxied by the external auditor turnover does not significantly affect the fraudulent financial reporting, which means that the variable is not able to detect fraud in financial reporting.